Kelly procedure for exstrophy or epispadias patients: Anatomical description of the pudendal neurovasculature. Issue 3 (June 2016) - Ben-Chaim, Jacob; Hidas, Guy; Wikenheiser, Jamie; Landau, Ezekiel H.; Wehbi, Elias; Kelly, Maryellen S.; McLorie, Gordon A.; Khoury, Antoine E.
Summary: Introduction: Adequate penile length in males with bladder exstrophy or epispadias is a major challenge. Kelly previously described a surgical technique of a single stage reconstruction for patients with exstrophy or epispadias that potentially achieves significant penile lengthening by completely detaching the insertion of the corpora cavernosa from the ischiopubic rami. However, because of the possibility of damage to the pudendal neurovascular supply that may lead to partial or complete penile loss, this technique has not gained popularity. The aim of this study is to describe the surgical anatomic relationship of the pudendal neurovascular bundle (NVB) to the ischiopubic rami and to determine a safer approach to dissection during the Kelly procedure. Methods: We performed meticulous dissection in three formalin-fixed and one fresh adult male cadavers to demonstrate the anatomical relationships between the pudendal neurovascular supply of the penis and the cavernosal insertion to the ischiopubic ramus. Results and discussion: We demonstrated the relationships and distance between the NVB and the area of separation between the crus and the ischiopubic ramus at the level of the periosteum. The insertion of the crus to the ischiopubic ramus is inferior lateral, whereas the NVB lies at a superior medial position. This anatomical relationship is best visualized when the dissection is carried out starting from the distal portion of the NVB and proceeding proximally. This area of the periosteum is avascular and the NVB can be preserved safely as long as the dissection is conducted at that subperiosteal level. Based on this cadaver dissection study, we suppose that detaching the corporal cavernosa from the pubic bones at the subperiosteal level allows for a safe distance to be maintained from the pudendal nerve at all times. We believe that if a surgeon performs the dissection inferiorly and laterally, the corpora cavernosa can be safely detached from the ischiopubic ramus and injury to the pudendal vessels and nerve can be avoided. However, it must be noted that there are limitations to applying the results from this study of normal, adult cadavers to the anatomy of children and adolescents with exstrophy or epispadias, who form the largest proportion of patients who are candidates for this procedure. Conclusion: This anatomical study demonstrates the relationship between the pudendal NVB, the crus, and the ischiopubic ramus. We demonstrated how the separation of the crus from the ischiopubic periosteum might be performed more safely. Figure Fresh cadaver dissection (A) before incision of the crus from the ischiopubic ramus, and (B) after incision of the crus from the ischiopubic ramus.